The Narrative of Morality and Media Discourse in the Closure of Payo Sigadung Red-Light District: A Literature and News Analysis: A LITERATURE AND NEWS ANALYSIS - Nurhasanah, Nurhasanah; Malik , Abdul (Journal of Southeast Asian Islam and Society, 2025)
AbstractThis research analyzes the narratives of morality and media discourse surrounding the closure of the Payo Sigadung red-light district in 2014, as well as its impact on sex workers and the surrounding community. Through a literature review and media analysis, the study reveals that the closure was dominated by conservative moral narratives in media coverage, which tended to simplify prostitution as solely a moral issue. Media outlets such as Kompas and Jambi Express portrayed the closure as a victory for religious values, while The Jakarta Post attempted to provide a more humanistic perspective by highlighting the impact on sex workers. The closure of the red-light district caused many sex workers to lose their primary source of income and struggle to find alternative employment, while the local community experienced a decline in economic income. The government's ambiguous response”closing the red-light district but failing to provide an effective reintegration program”worsened the situation. This study concludes that the closure of red-light districts requires a holistic approach, including economic empowerment, human rights protection, and a paradigm shift in media discourse. The research recommendations include skills training programs, healthcare services, and anti-stigma campaigns to support former sex workers.